Reported barriers to eating more fruit and vegetables before and after participation in a randomized controlled trial: a qualitative study. - John, J; Ziebland, S (2004)
This qualitative study compares the barriers to eating more fruit and vegetables reported before and after participation in a 6-month randomized controlled trial in primary care. At the initial intervention appointment of a primary care intervention to promote eating five or more portions of fruit and vegetables a day, participants were asked to identify the barriers that they thought they might encounter. Barriers were discussed again at the final appointment 6 months later. At the end of the study, a purposive sample of 40 of the trial participants was interviewed to explore their experiences in greater detail. Transcripts of tape recordings of the intervention appointments and the semi-structured interview were analysed using qualitative methods. This paper presents the results of a qualitative analysis of these appointment and interview transcripts (results of the trial are published elsewhere). Women reported that children and male partners were obstructive to their attempts to eat more fruit and vegetables, whilst men reported that their partners were supportive of the change. The perception that fruit and vegetables were expensive was a relatively intractable barrier for those with inflexible food budgets. Some barriers, including the problem of getting fruit and vegetables when travelling or when the daily routine is disrupted such as at weekends, were not anticipated and only encountered when participants tried to make changes. However, while all but three of the interview respondents described experiencing at least one barrier to eating more fruit and vegetables, three quarters (29 of 40) reported an increase in intake of between one and five daily portions. This study adds to the existing literature in that it investigates those barriers that were reported at the end of, as well as before, a 6-month trial of a dietary intervention. The findings show that trial participants were not always able to anticipate what might be a barrier to change at the initial intervention appointment. The flexible action plan meant that if participants found their initial plan hard to maintain, they were able to adapt it rather than give up. This suggests that health behaviour interventions that are negotiated and non-prescriptive may be more successful than those that are relatively inflexible.